Presuppositions in Jim Gaffigan’s jokes on “30 Minutes of Jim Gaffigan’s: Quality Time” on the Dynamics Comedy YouTube channel - Kinanthi, Eva Adeline; Hikmat, Mahi M.; Budiarti, Dian (Journal of Research on English and Language Learning (J-REaLL), 2025)
This study aims to analyze the use of presuppositions and implied meanings that create jokes in Jim Gaffigan's stand-up comedy show, “30 Minutes of Jim Gaffigan: Quality Time - Stand Up Comedy,” uploaded to the Comedy Dynamics YouTube channel. This study uses a qualitative method. The data analyzed are Jim Gaffigan's jokes that contain presuppositions. The results show that there are 23 data points containing presuppositions in Jim Gaffigan's jokes, categorized into 7 existential presuppositions, 5 non-factive presuppositions, 4 lexical presuppositions, 4 counterfactual presuppositions, 2 factive presuppositions, and 1 structural presupposition. Based on the study result, the presupposition that is often used in Jim Gaffigan’s jokes is existential presupposition. In conclusion, presupposition not only functions as a communication tool but also as a means to foster social connections through laughter. The impact of using presupposition in comedy is that it creates a quick connection between the comedian and the audience, thus strengthening the effectiveness of the joke. Choosing the right type of presupposition, such as existential, can make it easier for the comedian to deliver accessible humor, while the use of an inappropriate presupposition, such as structural, can reduce the humorous effect as it requires more time to think.